Economic Resistance of Sub-National Governments in Mitigating Inflation Risk: The Case of Bela Beli Kulon Progo Movement - Setiawan, Hendy; Irawan, Rizky Rahmanda; Erison, Yendra (Faculty of SociaI and Political Sciences (FISIP), Universitas Islam Negeri (UIN) Bandung, 2023)
Political decentralization has brought great changes in the form of challenges and opportunities. In the context of the challenges of decentralization, it requires regions to clean up, organize, and fix regional problems. However, it must be used as an instrument to solve economic problems, one of which is inflation in the regions. Kulon Progo Regency is one of the role models that has an economic instrument in mitigating the risk of inflation. This arrangement is stated in the Bela Beli Kulon Progo policy. This policy uses an approach to strengthen the local economy so that it can stimulate the growth of people's per capita income. This study examines these issues using a qualitative approach with library research methods. It uses the theory proposed by the decentralization and inflation approach proposed by Treisman. The results show that strengthening the local economy had the power to mitigate the risk of inflation in regions. The strengthening of the local economy was seen in the increasing level of people's income and regional income which resulted in stronger economic growth. However, inflation is a serious threat to the regional economy if people's incomes are fixed and there is economic instability. Bela Beli Kulon Progo movement improved the local economy of Kulon Progo. Various programs of Bela Beli became the basis for the strong economic support of the district so that inflation could be controlled. On this basis, the movement becomes an instrument as well as a role model in mitigating the risk of regional inflation. This study, therefore, contributes to the study of local movement and inflation in the regional contexts.